INTERDEPENDENCE OF HEREDITY, ENVIRONMENT AND UPBRINGING IN THE FORMATION AND DEVELOPMENT OF PERSONALITY - Matviiv, Nazar; Machynska, Nataliia (Continuing Professional Education: Theory and Practice, 2021)
The article is devoted to the analysis of the research of the Dutch professor Dick Ferdinand Swaab in the context of interdependence and interplay of heredity, environment and upbringing on the formation and development of personality. The authors, conducting a critical review of Dick Swaab’s publications, were focused on the important features of personality formation, integrating in this context information from psychology, pedagogy and neurobiology. The publication shows the close connection of all factors influencing the formation of personality; their interdependence and interdependence at different age stages of personality development are proved. Indicated clear correlation between research on neurobiology and pedagogy, in this context, mutual proven link between the sciences and their joint impact on people. It is determined that the fatal development of personality significantly depends on the individual characteristics of the material, shows the influence of bad habits of materials on genetic mutations in humans. It is shown that intellectual development is a complex process that depends on both the genetic makeup of the person and the environment. It is proved that upbringing and social interaction were and remain the drivers of cultural and civilizational formation of the individual at different age stages. Emphasis is placed on the fact that social contact is an important factor in hormonal processes within the human body; it is shown that the processes of personality formation are actively influenced by external factors (optimal proportion of movement and sleep, failure of the biological clock, stress, impaired fine motor skills, etc.). It is shown that economic status is one of the factors of intellectual development of children with developmental disabilities. The study, based on the basic practical results obtained by Professor Dick Swab, presents the need for a thorough study of these interdependencies and the relationship of students of pedagogical specialties in the context of providing training for future educators.